Associations of levels of biochemical markers of chronic and acute inflammation, abdominal obesity and post-COVID syndrome in COVID-19 convalescents - A. A. Karaseva; A. D. Afanaseva; E. V. Garbuzova; E. V. Kashtanova; Ya. V. Polonskaya; V. S. Shramko; I. I. Logvinenko; Yu. I. Ragino (Кардиоваскулярная терапия и профилактика)
Aim. To study the associations of abdominal obesity (AO), levels of biochemical markers of chronic and acute inflammation, and post-COVID syndrome (PCS) in coronavirus disease 2019 (COVID-19) convalescents.Material and methods. The cross-sectional observational study included 166 people aged 18-84 (44,6% men) who were COVID-19 convalescents. In all patients, medical history and anthropometric data were collected. AO was defined as waist circumference >80 cm in women and >94 cm in men. In the blood serum, the concentrations of following biochemical markers of chronic and acute inflammation were determined by the enzyme immunoassay method: interferon alpha, interleukins (IL) 1 beta (IL-1β), IL-6, IL-8, monocyte chemoattractant protein-1 (MCP-1), insulin, C-peptide, high-sensitivity C-reactive protein (hsCRP).Results. COVID-19 convalescents with PCS and AO had significantly higher levels of IL-6 (3,13 [2,26;4,98] and 1,74 [1,10;3,04] pg/ml, p<0,0001, respectively) and hsCRP (3,83 [2,42;10,16] and 2,34 [0,70;5,79] mg/l, p=0,028, respectively) than without AO. Insulin and C-peptide demonstrated significant differences in COVID-19 convalescents with AO regardless of PCS. Multivariate logistic regression analysis showed that the odds of having AO in COVID-19 convalescents with PCS increased by 1,6 times with an increase in blood IL-6 by 1 pg/ml (odds ratio (OR) 1,581, 95% confidence interval (CI): 1,001-2,416; p=0,047) and by 1,2 times with an increase in blood insulin by 1 pg/ml (OR 1,168, 95% CI: 1,015-1,343; p=0,030). AO in men with PCS is associated with the concentration of IL-6 (OR 1,943, 95% CI: 1,018-3,709; p=0,044) and IL-1β (OR 0,591, 95% CI: 0,362-0,967; p=0,036). PCS in women with AO and cardiovascular diseases is associated with the level of MCP-1 (OR 0,991, 95% CI: 0,983-0,999; p=0,035).Conclusion. In COVID-19 convalescents with PCS, the AO probability is associated with an increase in blood IL-6 and insulin. In men, the AO probability is associated with an increase in IL-6 and a decrease in IL-1β. In women with AO and a history of cardiovascular diseases, PCS is associated with the level of MCP-1 in the blood.